2013
DOI: 10.1177/0036933013482667
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of acute internal haemorrhage: cystic artery pseudoaneurysm secondary to acute cholecystitis

Abstract: Spontaneous cystic artery haemorrhage is a rare complication of acute cholecystitis. Here we describe a case report of this unusual cause of internal haemorrhage, and discuss the pathogenesis and management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nine of the patients showed no symptoms of GI bleeding. In one case, 3 rupture of the PsA of the cystic artery resulted in hemoperitoneum with GB perforation, so there were no hemobilia. The incidence of jaundice was 27.8% (10/36) and the typical three symptoms of hemobilia (Quincke's triad) were reported in 16.7% (6/36) of the cases reported in this review, compared with 32% to 40% reported in other literature.…”
Section: Discussionmentioning
confidence: 97%
“…Nine of the patients showed no symptoms of GI bleeding. In one case, 3 rupture of the PsA of the cystic artery resulted in hemoperitoneum with GB perforation, so there were no hemobilia. The incidence of jaundice was 27.8% (10/36) and the typical three symptoms of hemobilia (Quincke's triad) were reported in 16.7% (6/36) of the cases reported in this review, compared with 32% to 40% reported in other literature.…”
Section: Discussionmentioning
confidence: 97%
“…However, major haemobilia is more commonly associated with sepsis and inflammation producing a pseudoaneursym of the hepatic artery [5]. Typical features of a haemobilia include RUQ abdominal pain, obstructive jaundice, gastrointestinal haemorrhaging/ melena (Quincke's triad) [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…In haemodynamically unstable patients with clinical and radiological evidence of cystic artery haemorrhage, operative haemorrhage control is required and this enables concurrent cholecystectomy [6]. The 3 major modalities used to reveal and study the size, location, and morphology of an aneurysm include thin-section CT scanning after an intravenous injection using special computer software CT angiography [CTA]; MRA and catheter angiography [11].…”
Section: Discussionmentioning
confidence: 99%